Development of calcium silicate composites for bone tissue engineering / Mehdi Mehrali - Mehdi, Mehrali (2015)
Calcium silicate (CaSiO3, CS) ceramics is a promising bioactive material for bone tissue engineering, particularly for bone repair. However, the brittle nature and low fracture toughness of CS often result in premature fracture of implants. Hence, there is a need to improve the fracture toughness of CS without compromising its biocompatibility. In this project, CS ceramic composites with improved mechanical strength and comparatively high bioactivity were fabricated for load-bearing applications in bone tissue engineering. In the first step, calcium silicate hydrate (CSH), consisting of nanosheets, has been successfully synthesized assisted by a tip ultrasonic irradiation (UI) method using calcium nitrate (Ca (NO3).4H2O), sodium silicate (Na2SiO3·9H2O) and sodium dodecyl sulfate (SDS) in water. Systematic studies found that the reaction time of ultrasonic irradiation and concentrations of surfactant (SDS) in the system were important factors to control the crystallite size and morphology. Recent findings indicating the promising biocompatibility of graphene imply that graphene can be used as an additive to improve the mechanical properties of composites. Therefore, in the second step, we report a simple method for the synthesis of calcium silicate/reduced graphene oxide (CS/rGO) composites using a hydrothermal approach followed by hot isostatic pressing (HIP). Adding rGO to pure CS increased the hardness of the material by ~40%, the elastic modulus by ~52% and the fracture toughness by ~123%. Different toughening mechanisms were observed including crack bridging, crack branching, crack deflection and rGO pull-out, thus increasing the resistance to crack propagation and leading to a considerable improvement in the fracture toughness of the composites. The formation of bone-like apatite on a range of CS/rGO composites with rGO weight percentages ranging from 0 to 1.5 has been investigated in simulated body fluid (SBF). The cell adhesion results showed that human osteoblast cells (hFOB) can adhere to and develop on the CS/rGO composites. In addition, the proliferation rate and alkaline phosphatase (ALP) activity of cells on the CS/rGO composites were compared with the pure CS ceramics. In the third step, CS ceramic composites reinforced with graphene nanoplatelets (GNP) were prepared using hot isostatic pressing (HIP) at 1150°C. Quantitative analysis suggests that GNP plays a role in microstructure development and is responsible for the improved densification. A uniform distribution of 1 wt. % GNP in the CS matrix, high densification and fine CS grain size help to improve the fracture toughness by ~130%, hardness by ~30% and brittleness index by ~40% as compared to the CS matrix without GNP. The CS/GNP composites exhibit good apatite-forming ability in the simulated body fluid (SBF). These results indicate that the addition of GNP decreased the pH value in SBF. The effect of addition of GNP on early adhesion and proliferation of human osteoblast cells (hFOB) was measured in vitro. The CS/GNP composites showed good biocompatibility and promoted cell viability and cell proliferation. The results indicated that the cell viability and proliferation are affected by time and concentration of GNP in the CS matrix.